God's smuggler - Andrew, Brother (Chosen, 2017)
Millions have been awed by this riveting true-life spy story of a Dutch factory worker going undercover to take Bibles behind closed borders. Let this captivating illustrated edition for readers ages 9 to 12 introduce the young people in your life to one of the heroes of the faith--and the miraculous ways in which God leads those who follow his heart.